Genetic relationship and allozyme expression of insecticide susceptible and resistant helopeltis theivora populations from Peninsular Malaysia - Md Latip, Siti Noor Hajjar; Muhamad, Irita; Tan, Soon Guan (Universiti Putra Malaysia Press, 2005)
Helopeltis theivora is a known pest of cocoa and tea in Malaysia. Several mechanisms of insecticide resistance have been proposed such as reduction in the sensitivity of target sites, metabolic detoxification of pesticides and decreased penetration or translocation of pesticides. Polyacrylamide gel electrophoresis (PAGE) was used to determine the metabolic enzymes involved in the development of resistance in Helopeltis theivora. Adults of Helopeltis theivora were collected from three geographical locations namely Bukit Cheeding (Banting, Selangor), Sg. Palas (Cameron Highlands) and MARDI (Cameron Highlands, Pahang). In total, 25 enzymes were screened for polymorphisms and 8 enzymes were detectable in H. theivora. The dendogram resulting from the cluster analysis grouped the infrequently sprayed Banting and the MARDI populations together while the intensively sprayed Sg. Palas population clustered by itself.